Semiconductor to metallic transition in double halide perovskites Cs2AgBiCl6 through induced pressure: A DFT simulation for optoelectronic and photovoltaic applications. Issue 8 (August 2022) - Islam, Md. Nurul; Podder, Jiban
Abstract: Double halide perovskites (A2 M + M3 + X6 ) have been considered as high-performance material for optoelectronic and photovoltaic devices. Here, we investigate the structural, thermodynamic, optical, mechanical and electronic properties of pressure-induced Cs2 AgBiCl6 samples. The phase stability is confirmed by the tolerance and octahedral factor calculations. The thermodynamic potentials such as enthalpy, free energy, entropy, and heat capacity are observed in the phonon modes. The indirect to direct band gap is observed due to disorders of Ag + /Bi 3+ cations in their sub-lattice. In this study, the induced pressure was varied between 0 and 80 GPa and the transition of the band gap energy from semiconductor to metal was observed at a hydrostatic pressure of 80 GPa. The bond length in between Ag and Bi atoms is reduced due to crystal defect, occurred under induced pressure. The narrow band gap energy and the partial density of states of the disordered Cs2 AgBiCl6 samples refer to the relocation of charge carriers to facilitate the photocatalytic reaction. As the pressure changes, the absorbing edge also moves into the lower energy region. The pressure-inducted Cs2 AgBiCl6 sample has a strong absorption in the range of visible wavelength of light and shifted in the ultraviolet region. Simultaneously, the pressure-driven material extend the symmetry breaking of [AgBi] −6 and [AgCl] −6 octahedra and hence the total energy decreased due to narrow band gap energy. Phase-change dihalide materials have excellent properties, opening up new avenues for device applications. The mechanical properties suggest that the pure and pressure-inducted Cs2 AgBiCl6 samples have potential characteristics for an optoelectronic and photovoltaic applications. Abstract : Cs2 AgBiCl6 ; Phase stability; mechanical; optical; electronic properties; photocatalyst.